The Myth of the Fourth Industrial Revolution - Moll, Ian (Theoria (Pietermaritzburg), 2021)
This article argues that there is no such phenomenon as a Fourth Industrial Revolution. It derives a framework for the analysis of any industrial revolution from a careful historical account of the archetypal First Industrial Revolution. The suggested criteria for any socioeconomic transformation to be considered an industrial revolution are that it must encompass a technological revolution; a transformation of the labour process; a fundamental change in workplace relations; new forms of community and social relationships; and global socio-economic transformations. These transformations indeed characterise the Second and Third Industrial Revolutions. The aggregate of technical innovations in the latter is carefully examined, because this is a crucial part of determining whether we can meaningfully claim that a Fourth Industrial Revolution is underway. The article demonstrates that we cannot.